2022
DOI: 10.47577/tssj.v33i1.6775
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Experience, Satisfaction, and Trust of Y Generation Tourist Instagram Social Media Users to Tourism Destination Loyalty in Yogyakarta

Abstract: The purpose of this study is to understand the factors of Y Generation Instagram users in choosing tourism destinations, so that they can be a reference for community groups to develop innovative products based on potential resources and human resource competencies to design sustainable and competitive authentic products. This research uses quantitative method. Purposive sampling is a technique for determining research samples with certain considerations aimed at making the data obtained more representative. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Thus, tourists who always seek online information via social media platforms will be more interested and opt for the destination that provides valuable information and photos online (Țuclea, et al, 2020); [97] [98] also maintained that social media have a significant link with the travel decision-making process and destination choice. In addition to the above, [99] recently observed that active engagement on social media platforms with tourists positively affects tourism destination decision-making.…”
Section: Tourism Destination Decision Makingmentioning
confidence: 93%
“…Thus, tourists who always seek online information via social media platforms will be more interested and opt for the destination that provides valuable information and photos online (Țuclea, et al, 2020); [97] [98] also maintained that social media have a significant link with the travel decision-making process and destination choice. In addition to the above, [99] recently observed that active engagement on social media platforms with tourists positively affects tourism destination decision-making.…”
Section: Tourism Destination Decision Makingmentioning
confidence: 93%
“…Several investigations have been conducted to evaluate the increasing importance of digital marketing and its evolving strategies based on consumer preferences. Social media and websites are increasingly popular in marketing operations since they provide more personalized connections between consumers and vendors, strengthening the relationship and enhancing market involvement [13]. Online business marketing professionals create a content network on popular digital platforms like Facebook, Twitter, and Instagram, then switch to business-to-business social media platforms like LinkedIn to publish more specialized content [14].…”
Section: Digital Marketingmentioning
confidence: 99%